1991
DOI: 10.1007/bf01741331
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with treatment of human B cell lymphoma with anti-CD19 monoclonal antibody

Abstract: Six patients with progressive B cell non-Hodgkin's lymphoma have been treated with an IgG2a mouse monoclonal antibody (mAb) against the B cell differentiation antigen CD19, with total doses varying from 225 mg to 1000 mg. Free mAb was detected in the serum after doses of 15-30 mg. After the mAb infusions the number of circulating tumour cells was temporarily reduced, but in some cases antibody-coated cells remained in the circulation for several days. mAb penetrated to extravascular tumour sites; in general hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 23 publications
(14 reference statements)
1
36
0
1
Order By: Relevance
“…Serology results from 3 subjects indicate that the remaining CD19 Several CD19-directed antibody-based immunotherapeutic approaches are currently in clinical trials for the treatment of B-cell lineage malignancies. [40][41][42] Neither preclinical nor clinical studies using such approaches have addressed the fate of PC or preexisting antigen-specific antibodies. 7,40,43 The recent introduction of CD19-directed CAR T-cell-based therapy has provided a unique opportunity to study the impact of prolonged B-cell aplasia on the CD19 2 PC population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serology results from 3 subjects indicate that the remaining CD19 Several CD19-directed antibody-based immunotherapeutic approaches are currently in clinical trials for the treatment of B-cell lineage malignancies. [40][41][42] Neither preclinical nor clinical studies using such approaches have addressed the fate of PC or preexisting antigen-specific antibodies. 7,40,43 The recent introduction of CD19-directed CAR T-cell-based therapy has provided a unique opportunity to study the impact of prolonged B-cell aplasia on the CD19 2 PC population.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] Neither preclinical nor clinical studies using such approaches have addressed the fate of PC or preexisting antigen-specific antibodies. 7,40,43 The recent introduction of CD19-directed CAR T-cell-based therapy has provided a unique opportunity to study the impact of prolonged B-cell aplasia on the CD19 2 PC population. The duration of continuous B-cell aplasia in the cohort presented here, which was observed for at least 1827 days in 1 subject, depends on the duration of CAR T-cell persistence.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of naked anti-CD19 to its target does not necessarily lead to cell death or antitumor activity. In one study where mouse antihuman CD19 antibody was used to treat six patients with B-cell lymphoma, antibody-coated cells remained in the circulation of some patients for several days (30). The CD19 pathway can involve Src family kinases, lead to amplification of B7-1 and B7-2 costimulatory molecules, and activate T cells (31).…”
Section: Discussionmentioning
confidence: 99%
“…These have included unmodified anti-CD19 antibodies (8,9), antibody-drug conjugates (10)(11)(12), and bispecific antibodies targeting CD19 and CD3 (13) or CD16 (14) to engage cytotoxic lymphocyte effector functions. Although early clinical studies with murine unconjugated CD19 antibodies showed safety and responses in individual patients, these responses were not durable (15). However, recent phase I trials with bispecific antibodies have yielded encouraging results (16).…”
Section: Introductionmentioning
confidence: 99%